Proceedings of the seminar for Arabian studies. - Seminar for Arabian Studies (Oxford, UK)
viii, 350 sayfa
Keywords: “The Seminar for Arabian Studies is the principal international academic forum for research on the Arabian Peninsula. First convened in 1968 it is the only annual academic event for the study of the Arabian Peninsula that brings together researchers from all over the world to present and discuss current fieldwork and the latest research. The Seminar covers an extensive range of subjects that include anthropology, archaeology, architecture, art, epigraphy, ethnography, history, language, linguistics, literature, numismatics, theology, and more besides, from the earliest times to the present day or, in the fields of political and social history, to around the end of the Ottoman Empire (1922). The 53rd Seminar for Arabian Studies was hosted by the University of Leiden and took place in the Lipsius Building from Thursday IASA. In total sixty-five papers and twenty-three posters were presented at the three-day event. On Friday 12 July a special session on the stone tools of prehistoric Arabia was held, the papers from this session are published in a supplement to the main Seminar Proceedings” --